The capability dilemma in operational poverty assessment - Julia Johannsen; Manfred Zeller; Stephan Klasen (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2007)
This paper compares the standard economic welfare approach to poverty measurement to the empirical approaches proposed in the capability literature under the special focus of their suitability for operational poverty assessment, i.e. targeting and outreach evaluation. We question whether the measurement of per capita daily expenditures compared with a monetary poverty line justifiably remains the most widely used approach regarding poverty assessment. Its underlying value judgments and unsatisfactory assumptions differ considerably from those of the capability concept of poverty but the two approaches can be linked and critically compared with respect to the role of income, the conceptualisation of absolute poverty and the development of operational tools. We argue that despite the progress made in operationalizing the capability approach, there remain serious challenges when focussing on targeting and outreach evaluation and propose three alternative solutions for dealing with this capability dilemma in practice.
Keywords: 330; Armut; Disparitätsmaß; Wohlfahrtstheorie; Theorie